Design, synthesis and biochemical evaluation of novel 1,2,3,4-tetrahydroisoquinolines as anti-proliferative agents in breast cancer cells - Horan, Jason (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2009)
Isoquinolines are naturally occurring alkaloids that have shown biological activity in a number of different areas. In terms of breast cancer, tetrahydroisoquinoline based compounds have shown potential as selective estrogen receptor modulator (SERM). This class of compound show estrogenic effects in certain tissues and anti-estrogenic effects in other tissues in the body. Tamoxifen was the first SERM type compound utilised in the treatment of breast cancer. The objectives of the present work was to develop a series of novel compounds based on the tetrahydroisoquinoline scaffold with the ability to produce an anti-proliferative effect in estrogen receptor positive breast cancer cells.
Keywords: Pharmaceutical Chemistry, Ph.D.; Ph.D. Trinity College Dublin